Enhancing wind energy efficiency: A study on the power output of shrouded wind turbines for a hydrogen storage system - Seyyed Amirreza Abdollahi; Seyyed Faramarz Ranjbar; Moharam Jafarai; Mir Biuok Ehghaghi; Saman Faramarzi (Results in Engineering)
This study presents a simulation and analysis of a shrouded wind turbine system integrated with a proton exchange membrane electrolyzer (PEME) for hydrogen production. The novel aspect of this research lies in the use of an aerodynamic blade shroud to enhance the wind turbine's performance, particularly at low wind speeds. The addition of the aerodynamic shroud increases the power output by up to 68 % at a wind speed of 2.5 m/s, compared to a conventional wind turbine. Additionally, the effect of radial clearance between the shroud and turbine blades is explored, showing that a smaller clearance significantly improves power generation. The study also investigates the impact of blade shape (NACA 2408 and NACA 4418) on performance, with results indicating a 53 % increase in power output for the NACA 4418 design compared to the unshrouded turbine. The influence of the aerodynamic blade shroud on PEME energy density and hydrogen production efficiency is discussed, demonstrating how increasing wind turbine power output leads to higher current density in the electrolyzer, which, while increasing hydrogen production, slightly reduces thermal and exergy efficiencies. To counteract this, the study suggests using multiple PEME stacks in parallel to enhance both efficiency and hydrogen output.